On the Global Uniqueness of Fix-Price Equilibria - Schulz, Norbert (Econometrica, 1983)
[Fix-price equilibria à la Benassy are shown to be unique under a condition, closely related to the macroeconomic stability condition, at any price system p extgreater extgreater O.]